Impact of Temperature on Survival Rate, Fecundity, and Feeding Behavior of Two Aphids, Aphis gossypii and Acyrthosiphon gossypii, When Reared on Cotton - Jinping Liu; Chen Wang; Nicolas Desneux; Yanhui Lu (Insects, 2021)
Aphid performance is sensitive to temperature changes. Previous studies found that Acyrthosiphon gossypii (Mordviiko) was more sensitive to high temperature than Aphis gossypii (Glover). However, the effects of high temperatures on the survival, fecundity, and feeding behavior of these two aphid adults are not clear. This study examined the effect of different temperatures (29 °C, 32 °C, and 35 °C) on the adult survival rate, fecundity, and feeding behavior of these two aphid species. Our results showed that the adverse effects of high temperatures (32 °C and 35 °C) on aphid adult survival and fecundity were greater for Ac. gossypii than Ap. gossypii. The electrical penetration graph (EPG) data showed that Ac. gossypii spent more time feeding on xylem than phloem under all temperature treatments, which contrasted with Ap. gossypii. The time of phloem ingestion by Ap. gossypii at 32 °C was significantly higher than at 29 °C, while for Ac. gossypii, this value significantly decreased when temperature increased. These feeding patterns indicate that Ac. gossypii obtains less nutrition from phloem in support of its development and fecundity. Data generated in this study will serve as the basis for predicting the effects of increased temperature on these two cotton aphids.